Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Let the 2 numbers be x and y.
y = x + 30 ( as the difference between the two numbers is 30)
Sum of the two numbers = 100
=> x + y = 100
=> x + (x + 30) = 100 ( as y = x + 30 as shown above )
=> 2x = 70
=> x = 35
y = x + 30 = 65
Hope I helped! you may comment here if you have any further doubts and i will answer them :)
y = x + 30 ( as the difference between the two numbers is 30)
Sum of the two numbers = 100
=> x + y = 100
=> x + (x + 30) = 100 ( as y = x + 30 as shown above )
=> 2x = 70
=> x = 35
y = x + 30 = 65
Hope I helped! you may comment here if you have any further doubts and i will answer them :)
Let the two numbers be x and y.
According to your question ;
x + y = 100
x - y = 30
Thus. x = y + 30
Substituting the value of x,
y + 30 + y = 100
2y + 30 = 100
y = 70 / 2 = 35
thus, y = 35
Substituting the value of y,
x + y = 100
x + 35 = 100
x = 100 -35 = 65
x = 65.
thus, the two numbers are 65 and 35.
According to your question ;
x + y = 100
x - y = 30
Thus. x = y + 30
Substituting the value of x,
y + 30 + y = 100
2y + 30 = 100
y = 70 / 2 = 35
thus, y = 35
Substituting the value of y,
x + y = 100
x + 35 = 100
x = 100 -35 = 65
x = 65.
thus, the two numbers are 65 and 35.
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.